Renewable Energy Education from the Science, Technology and Society (CTS) Approach (2019)
The objective of this research project is to formulate a renewable energy education program for high school students of the Emilio Cifuentes Municipal Educational Institution from the CTS Approach; through a methodology applied with a mixed design. The theoretical review on the role of the teacher in renewable energy education is presented as results of the diagnostic phase. It concludes about the need to introduce topics related to renewable energy sources in the initial and continuous teacher training programs, since it is the teachers who with their teaching will be able to promote a trained and educated workforce, as well as raise awareness in the world population on the benefits of this technology.